Competition and succession in tamarisk stands: towards biological control using native plants - DeWine, John, author; Cooper, David J., advisor; Scott, Michael L., committee member; Steingraeber, David A., committee member; Stohlgren, Thomas J., committee member (Colorado State University. Libraries, 2006)
Tamarisk species (Tamarix ramosissima Ledeb., T. chinensis Lour., T. gallica L. and hybrids), have invaded riparian areas throughout western North America to the detriment of native plants and animals. Tamarisk is a relatively recent addition to North American plant communities, thus competitive and successional processes are still developing. Box elder (Acer negundo L. var. interius (Britt.) Sarg.) is a potential native competitor found in mid elevation canyons throughout western North America. Competition was studied through neighborhood analysis and succesional trends were analyzed through dendrochronology in mixed stands of box elder and tamarisk in the canyons of Dinosaur National Monument (DNM), Colorado. The shade tolerances of both species were compared through field based and greenhouse experiments. Box elder was the superior competitor; the presence of canopy box elders within one and two meters was significantly related to tamarisk but not box elder mortality. The presence of canopy tamarisk trees was not related to box elder or tamarisk mortality. Tamarisk establishment predated or was concurrent with box elder establishment on newly formed surfaces. Tamarisk initially dominated the canopy, but box elder eventually overtopped and killed the tamarisk. Box elder had superior shade tolerance to tamarisk, and maintained positive growth and survived under higher shade than tamarisk. The shade generated by box elder canopies was capable of killing mature tamarisks. Box elder seedlings were planted under tamarisk canopies to determine if tamarisk facilitates box elder seedling survival. Tamarisk and box elder stands were mapped to determine where the distribution of the two species intersects in DNM. Box elder seedling survival was tested across a range of abiotic gradients found in the canyons of DNM. Tamarisk facilitated box elder seedling survival, the distribution of tamarisk and box elder intersected in many areas, and seedling box elders survived and grew under the range of litter depth, soil texture, groundwater depth and shade intensities found in DNM. The manipulation of competitive and succesional processes through the promotion of box elder and other native tree establishment is suggested as a means of bottom up tamarisk control to complement traditional control techniques.
Keywords: botany; ecology